Comparative analysis of Basalt/E-Glass/S2-Fibreglass-Carbon fiber reinforced epoxy laminates using finite element method - Aslam Shaikh, A. (Elsevier Ltd, 2022)
This paper aims to numerically analyse (using finite element methods) the static loading effects on basalt/E-glass/S2-fibreglass-carbon fibre reinforced epoxy hybrid composites, an alternative to the conventional and expensive pure carbon fibre epoxy composites. Structural properties of few hybrid composites are evaluated through static tests for validation purpose. The composite specimens comprising of four layers of carbon fibre and four layers of either basalt/E-glass/S2-fibreglass combined with LY556 resin in six varying stacking sequences are analysed for failure based on Tsai-Wu failure criteria. Commercial finite element software ANSYS Composite PrepPost (ACP) and ANSYS Mechanical were employed for this study. All specimen dimensions, boundary conditions and loading were adopted as per ASTM Standards. Results and discussion are followed by a significant comparison of static test results between basalt, E-glass, and S2-fibreglass each combined with carbon fibre epoxy. Finally, the optimal stacking sequence was found to be S2 - 02C/Â±45 M/0MS. Basalt-carbon hybrids produced superior results in tensile and flexural tests while the brittle glass-carbon hybrids proved to be better in compression and in-plane shear. Laminates with carbon fibre at the outer layers showed improved performance among contemporaries. Â© 2022